CRIMINAL LAW CHARACTERISTIC OF AN IMPERSONAL VOTE (ARTICLE 364-2 OF THE CRIMINAL CODE OF UKRAINE) - Lykhova, Sofia Ya.; Lychak, Volodymyr V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: criminal law characteristic of criminal offence, juridical content of which is provided in the disposition of ar. 364-2 of the Criminal Code of Ukraine. Historical legal, comparative legal, dialectical, logical semantic and other general scientific and special methods of cognition, with the help of which authors make criminal legal characteristic of criminal offence, judicial content of which is provided in the disposition of ar. 364-2 of the Criminal Code of Ukraine, form the methodological base of an investigation. Results: the judicial content of criminal offence, which is provided in the disposition of ar. 364-2 of the Criminal Code of Ukraine, was characterised, additional arguments on the separation of this criminal offence in a separate content were given. Discussion: authors suggest detailing the disposition of ar. 364-2 of the Criminal Code of Ukraine.